(untitled) - Rein, David P. (New York, 1982)
The Language of Advertising and Merchandising in English is a neccessity for any budding communications student, or indeed for anyone who is really keen to pursue a career in these dynamic areas. It provides a perfect backdrop to the whole world of marketing of products, images and ideas, and goes into great detail in explaining the difficult concepts and all the in-jargon
Keywords: English language,Advertising,Merchandising